Principles of construction of ultrasonic tomographs for solution of problems of nondestructive testing in mechanical engineering; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Bolotina I. O. Irina Olegovna; Bulavinov A.; Pinchuk R.; Salchak Ya. A. Yana Alekseevna (Mechanical Engineering Processes and Metal Treatment, 2016)
Title screen